Effects of feeding poultry beds on the performance, digestibility and economics in finishing pigs - Bellaver, Claudio; Fialho, Elias Tadeu; Protas, José Fernando; Grumann, Astor (Pesquisa Agropecuaria Brasileira, 2014)
A complete randomized design with four treatments and five replications was carried out using 220 crossbred Landrace x LargeWhite pigs of both sexes from an average of 53.56 kg up to an average of 93.53 kg. The treatments used 0, 10, 20 and 30% of poultry waste in isoproteic rations. The poultry waste came from eight different broiler farms that use wood shavings as bedding. Four broiler lots were raised on the same bedding. This bedding was then collected, sifted and dehidrated by the sun. The results showed increases on daily gain up to the level of 7.17% poultry waste in the ration. Te lard thickness and feed efficiency decreased as poultry waste was increased in the diet. It was concluded that there were no economic benefits in using poultry waste in finishing rations for pigs.